Da moda às modas no vestuário: entre a teoria hierárquica e o pluralismo, pelo olhar da consumidora popular em Belo Horizonte - Luciana Crivellari Dulci (2009)
This work proposes a comparative analysis concerning two moments of fashion in clothing. The first one refers to the sociological theories that initially comprehended the phenomenon of fashion as a symbolic hierarchy between classes that dictate and classes that copy fashion. This perspective explained fashion, since its appearance in thewestern world until mid-20th century. The second time concerns to the fashion plural contemporary, which can no longer be explained through this perspective. Today there are various groups of fashion, in a plural existence that, when it comes to creation and renovation, does not reproduce the movement observed until the 1950s. The investigation aimed to highlight regularities and singularities between different contexts of fashion in clothes, mentioned here, by examining until what point the analytical proposal of symbolic hierarchy explains the fashions of today. Also, with this intention, an empirical research was done with the popular feminine consumers in the city of Belo Horizonte, representing, these consumers, a group of fashion within the plurality of thepresent time. The research was done to purchase information about their perceptions of social meanings related to the use of clothing, as well as their behaviour and their motivations of the acts of consumption of elements of clothing.